Allogeneic CD19-CAR-T cell infusion after allogeneic hematopoietic stem cell transplantation in B cell malignancies - Liu, Jun; Zhong, Jiang F.; Zhang, Xi; Zhang, Cheng (Journal of hematology and oncology, 2017)
Background Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is considered the cornerstone in treatment of hematological malignancies. However, relapse of the hematological disease after allo-HSCT remains a challenge and is associated with poor long-term survival. Chimeric antigen receptor redirected T cells (CAR-T cells) can lead to disease remission in patients with relapsed/refractory hematological malignancies. However, the therapeutic window for infusion of CAR-T cells post allo-HSCT and its efficacy are debatable. Main body In this review, we first discuss the use of CAR-T cells for relapsed cases after allo-HSCT. We then review the toxicities and the occurrence of graft-versus-host disease in relapsed patients who received CAR-T cells post allo-HSCT. Finally, we review clinical trial registrations and the therapeutic time window for infusion of CAR-T cells post allo-HSCT. Conclusions The treatment of allogeneic CAR-T cells is beneficial for patients with relapsed B cell malignancies after allo-HSCT with low toxicities and complications. However, multicenter clinical trials with larger sample sizes should be performed to select the optimal therapeutic window and confirm its efficacy.